The Effect of Combustion Tube Diameter on Flame Characteristics and Water Heating Time on Multifuel Stove - Satya Putra Gantada, Muhammad; Sari Wijianti, Eka; Setiawan, Yudi; Rodiawan, Rodiawan; Ariksa, Jeri (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Multifuel stove is an innovation of conventional stove that has the advantage of being able to use various types of fuel. In its operation, multifuel stove consists of many important components, one of which is the combustion tube. This study aims to find out the effect of variations in the diameter of the combustion tube on the characteristics of the flame and water temperature during the heating process. The method used in this study is a combination of experimental studies and literature studies. The variations in the diameter of the combustion tube tested were 4, 5, and 6 inches using used oil and kerosene as fuel. The test results showed that increasing the diameter of the combustion tube tended to accelerate the extinguishing of the fire, this was influenced by a phenomenon called the quenching effect. Meanwhile, the flame temperature tended to be lower with increasing tube diameter. The color of the flame and the temperature of the water were not too influenced by variations in tube diameter and type of fuel. The highest flame temperature was recorded on a 4-inch cylinder with used oil fuel, reaching 719.2 °C, while the longest flame duration was 16.92 minutes on a 4 -inch cylinder with used oil fuel. In conclusion, the performance of used oil can exceed that of kerosene.